Evaluation Of Pain in Ambulatory Hysteroscopy and Its Acceptance and Satisfaction (Journal of Pharmaceutical Negative Results, 2023)
Aims: To assess pain by visual analogue scale (VAS) and determine associated factors on pain experienced during ambulatory hysteroscopy (AH) without anaesthesia. To assess the patient acceptability and satisfaction after AH.Material and Methods: AH was performed in 75 patients using the vaginoscopic approach. Pain intensity was assessed using VAS. Factors determining pain & patient acceptability & satisfaction using respective questionnaires were evaluated.Results: Mild pain was experienced by 66% of patients, 22% moderate pain, and 12% severe pain. Patients who accepted the procedure & also showed a willingness to undergo the same procedure a second time were 86% and 82 % of patients were highly satisfied. Acceptability & satisfaction rate was found lower in patients with severe pain.Association of determining factors like nulliparity, menopausal status, cervical pathology and duration of the procedure for moderate pain, and presence of cervical & uterine pathology for severe pain during AH.Conclusion: Hysteroscopy is a gold standard, safe, and well-accepted procedure. Pain is the most common reason for the procedure being less accepted & a reduction in the satisfaction rate. Cervical pathology was a significant factor associated with pain during AH.